2017
DOI: 10.1016/j.apenergy.2017.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modeling of a microbial fuel cell considering anodic electron flow and electrical charge storage

Abstract: To describe the anodic electron flow and electric charge storage behavior of an MFC system from an electrical perspective, a dynamic model based on a novel electrical equivalent circuit is developed. Conventional equivalent circuits typically have series impedance to model the system from the standpoint of terminal quantities: output voltage and current. However, the conventional approaches do not properly explain internal anodic electron flow and double-layer charge storage characteristics of MFCs. The propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…in 2012 showed that cytochromes were able to store electrons and therefore the capacitive features of the anodes were shown 99 . Several examples related with the anode supercapacitive properties related to the different utilized materials were freshly presented 100 102 . In parallel, anode and cathode electrodes of a MFC were lately explored as the negative and positive electrodes of an internal supercapacitor (SC-MFC) 46 , 53 , 96 98 .…”
Section: Introductionmentioning
confidence: 99%
“…in 2012 showed that cytochromes were able to store electrons and therefore the capacitive features of the anodes were shown 99 . Several examples related with the anode supercapacitive properties related to the different utilized materials were freshly presented 100 102 . In parallel, anode and cathode electrodes of a MFC were lately explored as the negative and positive electrodes of an internal supercapacitor (SC-MFC) 46 , 53 , 96 98 .…”
Section: Introductionmentioning
confidence: 99%
“…1 a). The same concept was previously exploited to demonstrate a supercapacitive microbial fuel cell [68] , [69] , [70] , [71] , [72] . Here, the concept is applied to a MDC device to improve both power/current generated and desalination efficacy.…”
Section: Principle Of a Supercapacitive Microbial Desalination Cell (mentioning
confidence: 94%
“…This methodology was previously presented [68] , [69] , [70] , [71] , [72] . In previously reported literature, the supercapacitive properties of the electrodes were tested in MFCs [68] , [69] , [70] , [71] , [72] , whereas in this current work the same features were exploited and utilized in operating MDCs. Here, we demonstrate that these features not only increase the power/current output but also enhance the reduction in salt content.…”
Section: Methodsmentioning
confidence: 99%
“…parameters in Table 1 are chosen based on the method mentione experimental tests in the nominal state. In a stack with ns series cell parallel branches, the following parameters can be used in the mod The considered model for the EMG-BES cell is shown in Figure 3 [10,28]. The model parameters in Table 1 are chosen based on the method mentioned by [10] and data of experimental tests in the nominal state.…”
Section: Emg-bes Stackmentioning
confidence: 99%
“…This represented a milestone for the development of likely processes, producing different added-value chemicals and fuels from CO 2 and renewable energy surplus [17]. The process is performed under mild operational conditions (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) • C and atmospheric pressure) and is driven by electroactive microorganisms, without the need of an expensive catalyst, meaning higher energy efficiency and potentially lower construction and operational costs compared to chemical methanation [18]. Thus, P2G based on EMG-BES represents an innovative and flexible energy storage technology for renewable energy surplus (RES) management.…”
Section: Introductionmentioning
confidence: 99%